PENCEMARAN AIR DI SUNGAI CIPANAWUAN AKIBAT PEMBUANGAN SAMPAH TPA SARIMUKTI: Water Pollution of the Cipanawuan River Due to the Disposal of Garbage From the Sarimukti Landfill - Zakiyah Dwi Hasanah; Irene Mariane (AMICUS CURIAE, 2025)
The environment has an important role in human life. However, there are often environmental problems, especially regarding water pollution. The formulation of the problem studied is how to regulate water pollution in the river and the responsibility of the Sarimukti Landfill for water pollution in the Cipanawuan River. The type of research used is normative legal research, and the nature of descriptive research, then the conclusion is drawn deductively. The result research and conclusion is the water pollution caused by the Sarimukti final processing site has violated the river water quality standards set out in Article 113 paragraph (3) listed in Appendix VI of Government Regulation Number 22 of 2021. As well as violating the leachate quality standards stipulated in Article 3 paragraph (2) in Appendix I of the Regulation of the Minister of Environment and Forestry Number 59 of 2016 and UPTD PSTR as the technical implementing unit has established Standard Operating Procedures, the Sarimukti Landfill has carried out its responsibilities only technically, by article 87 of Law Number 32 of 2009 concerning Environmental Protection and Management, responsibility must be in the form of providing compensation. However, based on standard operating procedures that have been established, there is no regulation regarding compensation mechanism for water pollution.